EFFECT OF EXERCISE BENCH PRESS AND SITTING CALF WITH CHEST PRESS AND LEG PRESS TO POWERARM MUSCLE AND POWER LIMB MUSCLES - Choirul Umam; Oce Wiriawan; Edy Mintarto (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
This research aims to examine:1) How big the effectofbench press and sitting calf exercises to arm muscle power and leg muscle power; 2) How big the effect of chest press and leg press exercises to arm muscle power and leg muscle power; 3)How big the effect difference between bench press and sitting calf exercises and chest press and leg press exercises to to arm muscle power and leg muscle power. Research subject was boy student of SMA Negeri 1 Manyar as many 36 students, with age span 15-17 years which divided to three groups. Experiment group I received bench press and sitting calf while the second ones received chest press and leg press and the third experiment group performed activities according to daily routines. This type of research was applied quantitative research with quasi experimental research methods. The research design applied non-randomized control group pretest-postest design. And data analysis used were t-test and MANOVA. The data collecting process was using a medicine ball to obtain arm muscle power data and jump DF for leg muscle power during pretest and posttest. The results showed the difference between the pretest and posttest means of each group, namely: experimental group I for arm muscle power = 28.3 leg muscle power = 51.1. The second experiment group for arm muscle power = 45.9, leg muscle power = 78.2. Experiment Group III for arm muscle power = 13.3, leg muscle power = 27.1. Based on the above analysis, it can be concluded that there was an increase in all dependent variables for each experimental group after received bench press and sitting calf, chest press and leg press exercises, whereas chest press and leg press exercises were more effective at increasing arm muscle power and leg muscle strength Keywords: Weight training, Bench Press, Calf Sitting, Chest Pres, Leg Press, Arm Muscles Power, Leg Muscle Power.